Analytical solution for temperature equation of a fin problem with variable temperature-dependent thermal properties: Application of LSM and DTM-Pade approximant - Alhejaili, Weaam; Varun Kumar, R.S.; El-Zahar, Essam Roshdy; Sowmya, G.; Prasannakumara, B.C.; Ijaz Khan, M.; Yogeesha, K.M.; Qayyum, Sumaira (Chemical physics letters, 2022)
The closed-form solution is obtained using LSM and DTM techniques. [Display omitted] •Role of longitudinal fin in chemical process industries and LHTES is mentioned.•The thermal distribution in a longitudinal fin is addressed in this research.•Convection and radiation phenomenon are considered in predicting the heat transfer rate through the fin.•The temperature-dependent internal heat generation is incorporated in formulating the fin problem.•Rosseland approximation is considered for the radiation heat transfer. Temperature variation through a longitudinal fin with linear and nonlinear temperature-dependent thermal conductivities and heat transfer coefficient, subject to radiative heat flux and convective heat transport is explained in the present examination. For the radiative heat flux, the Rosseland approximation is incorporated and convection mode of energy transmission is accounted on the fin's surface. The associated physical problem is developed in such a manner that the steady-state heat transmission problem is governed with the help of dimensionless variables signified by a second order differential equation (ODE). To solve this equation, an analytical approach, DTM-Pade, and the LSM are implemented. Moreover, the consequence of a few non-dimensional factors on the temperature field are depicted graphically. The investigation's main findings illustrate that a significant decline in the thermal field is caused by an increment in the convection and the radiation mechanism. The internal development of heat affects the thermal distribution in the fin.